CONVENTIONAL AND RECENT DIAGNOSTIC AIDS IN TUBERCULOUS LYMPHADENITIS: A BRIEF OVERVIEW - Hasan, Shamimul; Saeed, Shazina (Asian Journal of Pharmaceutical and Clinical Research, 2017)
One of the most common form of extra-pulmonary tuberculosis is peripheral tuberculous lymphadenitis and accounts for 20-40% of the cases. Tuberculous lymphadenitis has a gender and age predilection (usually seen in young females).Â It is usually bilateral in presentation and is non-contagious. Recent upsurge in HIV co-infection has challenged the diagnosis and management of tuberculosis and of associated lymphadenopathy. In the endemic areas, tuberculous lymphadenitis remains an important and essential differential diagnosis in patients presenting with cervical swellings.Â A timely and accurate diagnosis is mandatory to overcome this public health threat. Interdisciplinary involvement of varied medical and dental professionals enhances the possibility of an effective and timely diagnosis of this condition.Â Keywords: Cervical lymphadenopathy, Diagnosis, Management, Tuberculosis.